EVOLUTION, ADVANCES AND PERSPECTIVE OF THE INVESTIGATION IN A VENEZUELAN PEDAGOGICAL UNIVERSITY (2012)
The present article approaches about thematic that bellows to the evolution, advances and perspective of the Investigation in the Pedagogical University Experimental Liberator (UPEL). It considers like investigation of documentary and descriptive character, whose intention is to exhibit the present state research in the UPEL. With such aim historical aspects are reviewed, structural and of relevance of the research. One is that in historical happening of the investigation in the university, elements are appraised that have made drowsy this function, concrete in the characterization of the works of research; nevertheless, the presence of legal instruments and the constant reformulation of the policies of financing of the research has given to a new sense and impulse it. Similarly one settles down that one of the enhancing variables of the research, is the organizational structure and managemental of the research in the university. In order to give an answer to relevance, we characterized in five categories the research realized in the UPEL, which is exposed in a brief way. Finally, there are some aspects that indicate that the research in our University tends to fortify itself, and ideas for their advance and consolidation.